2020
DOI: 10.14740/jmc3517
|View full text |Cite
|
Sign up to set email alerts
|

Cardiogenic Shock due to COVID-19-Related Myocarditis in a 19-Year-Old Autistic Patient

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is mainly responsible for respiratory involvement but cardiac complications are also reported. Nevertheless, potential life-threatening conditions in young people have not been described. A 19-year-old male autistic patient was admitted with fever and cough. The chest radiography showed viral pneumonia and the nasopharyngeal swab detected SARS-CoV-2. He rapidly developed hypotension, oliguria and increased myocardial injury markers and was treated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…A retrospective study by Finn et al reported a mortality rate as high as 61% in patients with acute myocarditis [ 46 ]. Although more common in patients with a documented medical history, there were several cases of myocarditis in patients without significant medical history, especially in the younger population [ 40 , 42 , 45 , 47 ]. Patients without underlying medical problems were also associated with better outcomes [ 19 , 40 , 42 , 45 ].…”
Section: Reviewmentioning
confidence: 99%
“…A retrospective study by Finn et al reported a mortality rate as high as 61% in patients with acute myocarditis [ 46 ]. Although more common in patients with a documented medical history, there were several cases of myocarditis in patients without significant medical history, especially in the younger population [ 40 , 42 , 45 , 47 ]. Patients without underlying medical problems were also associated with better outcomes [ 19 , 40 , 42 , 45 ].…”
Section: Reviewmentioning
confidence: 99%
“…Some patients may also present with palpitations alongside their other symptoms [ 67 , 71 ]. After initial presentation, patients may deteriorate to develop signs of heart failure and hemodynamic compromise if treatment is not initiated or is inadequate [ 9 11 ]. In severe cases, patients may initially present with new-onset heart failure in the absence of a history of cardiovascular disease [ 71 ].…”
Section: Presentation Of Covid-19 Myocarditismentioning
confidence: 99%
“…The disease course of COVID-19 myocarditis can range from mild to severe. If not treated, the myocarditis may progress to life-threatening heart failure and arrythmias; therefore, it is imperative for clinicians to recognize possible cases of COVID-19 myocarditis and treat them accordingly [ 9 11 ]. Moreover, it may lead to an increase in ward admissions in a time where hospitals can already be overwhelmed.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the rapid increase in the number of patients suffering from this unpredictable disease, the aim of physicians working on first line should be to know in depth its pathophysiology, clinical evolution and short and long-term consequences. Today, pneumonia remains the major clinical manifestation of COVID-19 [2] but, however, the onset of the disease have highlighted severe features previously unthinkable in patients, even in young patients with no previous pathology [3,4].…”
Section: Introductionmentioning
confidence: 99%